Theoretical research on the wear characteristics of rotors in a twin-screw compressor. (April 2022) - Wang, Chuang; Xing, Ziwen; Sun, Shizhong; Chen, Wenqing; He, Zhilong
Thanks to the development and application of coating technology and polymer rotor material, it is an inevitable trend to eliminate synchronous gear for water-injected and dry twin-screw compressors, especially running at a high speed, due to much power consumed by synchronous gears. However, it is not economical and reliable to rely only on coating or rotor material to enhance the wear resistance of rotor. This paper attempts to lighten the rotor wear in twin-screw compressors from the angle of setting driving belt. To achieve this goal, the contact analysis is carried out in this paper, taking the rotor profile of a developed water-lubricated twin-screw air compressor as an example. By the contact analysis, equivalent curvature radius, Hertz contact stress, sliding distance, the value of P H S, and the minimum film thickness of each mesh point on different tooth curve are calculated and discussed. The product of the Hertz contact stress and total sliding distance, P H S, and minimum film thickness are chosen as the evaluation indexes to estimate the wear resistance of all tooth curves. By comparing these indexes of each tooth curve, some suggestions about setting the driving belt are proposed.